DEGREE AND RELATIONSHIP OF INCREASING THE CREATIVE ACTIVITY OF STUDENTS OF TECHNICAL HIGHER EDUCATION IN THE PROCESS OF TEACHING FOREIGN LANGUAGES - Yakhoeva Gulnora Bakhtiyarovna (Journals Park Publishing, 2022)
The article examines the level and relationship of increasing the creative activity of students of technical higher educational institutions in the process of teaching foreign languages. The project method serves as the basis of cognitive and creative activity of students in foreign language learning activities in technical higher education institutions.
Keywords: technical higher education institution, student, creative activity, foreign languages